2018
DOI: 10.1080/09540121.2017.1417532
|View full text |Cite
|
Sign up to set email alerts
|

Racial and socioeconomic disparities in the symptom reporting of persons living with HIV

Abstract: Persons living with HIV (PLWH) today can survive decades with the disease, making the symptom experience much more relevant to their lifestyle and health outcomes. The goal of the research reported here was to assess the symptom reporting of PLWH in the Unites States (US) in the combined antiretroviral therapy (cART) age of the epidemic. We conducted an anonymous online survey of symptomatic PLWH in the US and asked participants to report the frequency and intensity of 28 frequently occurring symptoms in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…Despite this, the symptom experience of WLWH in the context of the female reproductive cycle has been largely understudied or compared to men. In one of the first online national surveys of 1373 PLWH (mean age of 48.5 years) where co-morbid conditions were common and the majority (92%) were receiving cART, 21 we reported that fatigue, depression, muscle aches/pains, and difficulty falling asleep were the most frequently reported symptoms, with significant race/ethnicity and income differences evident in symptom burden. In this sample, composed of 70% males, sex differences in symptom burden were few: only muscle aches and pains, reported as the third most common symptom next to depression and fatigue, was associated with higher burden scores in women vs. men, although strong trends were observed for fatigue and staying asleep.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Despite this, the symptom experience of WLWH in the context of the female reproductive cycle has been largely understudied or compared to men. In one of the first online national surveys of 1373 PLWH (mean age of 48.5 years) where co-morbid conditions were common and the majority (92%) were receiving cART, 21 we reported that fatigue, depression, muscle aches/pains, and difficulty falling asleep were the most frequently reported symptoms, with significant race/ethnicity and income differences evident in symptom burden. In this sample, composed of 70% males, sex differences in symptom burden were few: only muscle aches and pains, reported as the third most common symptom next to depression and fatigue, was associated with higher burden scores in women vs. men, although strong trends were observed for fatigue and staying asleep.…”
Section: Introductionmentioning
confidence: 83%
“…As reported in the parent study, we conducted an anonymous, cross-sectional online survey of the symptom profile of 1373 PLWH in the US from February to August 2016. 21 Study participants from the US were recruited through banner ads placed on five large social networking websites. Participants were eligible for the study if they were HIV+, 18 years or older, able to read and respond in English, resided within the US, reported having experienced at least one bothersome symptom in the past 30 days, and were willing to participate in an online survey about their health.…”
Section: Methodsmentioning
confidence: 99%
“…Given the scores on the eHEALS instrument, there is evidence to support the use of consumer eHealth tools, such as the mVIP app, to inform clinical decision making and health promotion. In summary, given these findings in Birmingham, AL, and other recent studies on symptom burden in the United States (Schnall, Cho, et al, 2018; Schnall, Siegel, et al, 2018; N. L. Wilson et al, 2016), there is strong scientific premise to support the feasibility of a mobile-delivered symptom self-management tool in the Deep South and other U.S. communities for improving health outcomes for PLWH in the United States.…”
Section: Discussionmentioning
confidence: 82%
“…L. Wilson et al, 2016). In our national online survey ( N = 1,373), there was a high symptom burden with fatigue, depression, muscle aches and pain, sleep difficulties, and anxiety being the most prevalent symptoms, and neuropathy being one of the most burdensome symptoms and affecting over 25% of our study participants (Schnall, Siegel, Jia, Olender, & Hirshfield, 2018). In our New York City in-person study ( N = 80), our participants also reported a high prevalence of symptoms with fatigue being the most frequently reported symptom ( N = 61, 76.3%), followed by difficulty falling or staying asleep ( N = 59, 74.7%), neuropathy ( N = 46, 59.0%), anxiety ( N = 45, 57.0%), and depression ( N = 43, 53.8%) (Schnall, Cho, Mangone, Pichon, & Jia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Results from the symptom reporting and self-management strategies are reported elsewhere. (34, 35) All study procedures and materials were approved by the lead investigator’s Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%